2006
DOI: 10.1097/01.wnr.0000221829.87974.ad
|View full text |Cite
|
Sign up to set email alerts
|

Increased body weight in mice lacking mu-opioid receptors

Abstract: Opioids have been suggested to affect feeding behaviour. To clarify the role of mu-opioid receptors in feeding, we measured several parameters relating to food intake in mu-opioid receptor knockout mice. Here, we show that the knockout mice had increased body weight in adulthood, although the intake amount of standard food was similar between the wild-type and knockout littermates. Serum markers for energy homeostasis were not significantly altered in the knockout mice. Hypothalamic neuropeptide Y mRNA, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…VTA MOR knockdown rescued the deficit of weight gain 10 days after the last episode of stress, but not during stress exposure. That knockdown of VTA MORs attenuated and promoted recovery from social stress-induced weight gain deficit is consistent with a report of increased body weight in MOR knockout mice (Han et al, 2006). Another study using the same lentiviral construct in the VTA (Lasek et al, 2007) also showed no significant effect on weight, indicating that VTA MOR knockdown is not sufficient to alter weight gain in the absence of social stress.…”
Section: Discussionsupporting
confidence: 91%
“…VTA MOR knockdown rescued the deficit of weight gain 10 days after the last episode of stress, but not during stress exposure. That knockdown of VTA MORs attenuated and promoted recovery from social stress-induced weight gain deficit is consistent with a report of increased body weight in MOR knockout mice (Han et al, 2006). Another study using the same lentiviral construct in the VTA (Lasek et al, 2007) also showed no significant effect on weight, indicating that VTA MOR knockdown is not sufficient to alter weight gain in the absence of social stress.…”
Section: Discussionsupporting
confidence: 91%
“…In some cases, the gene-targeting studies have contradicted the preponderance of pharmacological studies showing the ability of -opioid agonists to stimulate fat intake. This discrepancy has been most often ascribed to compensatory changes resulting from chronic inactivation of the Oprm1 gene that is not observed upon acute injection of -opioid ligands (12). In other cases, gene-targeting studies using different Oprm1 mutant mice have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pharmacological studies have demonstrated that stereotactic injection of a -opioid agonist into the nucleus accumbens preferentially stimulates the intake of high-fat food (48,50,52), whereas an antagonist selectively blocks this response (8,48). Finally, gene-targeting studies have reported that mice lacking Oprm1 show increased weight gain on standard chow (12), reduced weight gain on a high-fat diet (38), diminished food anticipatory activity (15), decreased motivation to seek food (28), and attenuated psychomotor sensitization in response to morphine (49).…”
mentioning
confidence: 99%
“…There is some evidence that MOR KO mice exhibit reduced or otherwise altered food-motivated behaviors (Kas et al 2004; Laurent et al 2012; Papaleo et al 2007), but it is unclear if this reflects a reduction in the experienced palatability of foods or a deficit in processing other qualities of foods that contribute to the acquisition and/or expression of conditioned behaviors (i.e., its ability to reinforce or motivate reward-seeking). Arguing against the palatability hypothesis is the observation that MOR KO mice maintained on normal (Han et al 2006) and high fat (Tabarin et al 2005) diets show normal levels of food intake when measured over long periods. However, monitoring feeding over such long intervals may not reveal the specific influence of food palatability on ingestive behavior (Frisina and Sclafani 2002; Higgs and Cooper 1998).…”
Section: Introductionmentioning
confidence: 99%